The impact of artificial intelligence on organizational performance: The mediating role of employee productivity - Belayneh Yitayew Kassa; Eyob Ketema Worku (Journal of Open Innovation: Technology, Market and Complexity)
The adoption of Artificial intelligence (AI) technology in the workplace is becoming more common, with several research highlighting both its positive and adverse influence on employee productivity (EP) and organizational performance (OP). Furthermore, there is a scarcity of research focused on the mediator role of EP in the nexus between AI and OP. This ambiguity underscores the need for a comprehensive understanding of how AI interacts with EP and OP within specific organizational contexts, such as Ethio Telecom. Therefore, this study aimed to investigate the impact of AI on OP with a mediating role of EP. Quantitative data was collected through an online survey using Kobo Toolbox from 172 purposively selected employees. AI was modeled as third-order formative construct, while EP and OP were first-order reflective constructs. The variables were measured using validated multi-item questionnaires with a 7-point Likert scale. The association between these variables was investigated with PLS-SEM in SMART PLS 4.1.03. The results showed that there were positive and significant relationships between AI and EP, AI and OP, EP and OP, and AI on OP through EP. Furthermore, EP served as a partial mediator between OP and AI. These findings are consistent with previous studies and theories, such as the resource-based view and human capital theories. The results suggest that organizations can dramatically improve performance in the digital age by implementing AI and creating a work environment that encourages productivity.